The nuclear stellar core, the hot dust source, and the location of the nucleus of NGC 1068 - Thatte, N; Quirrenbach, A; Genzel, R; Maiolino, R; Tecza, M (Institute of Physics Publishing, 1997)
We present new near-infrared speckle and adaptive optics imaging and integral field spectroscopy of the nuclear region of NGC 1068. Ninety-four percent of the K-band light in the central 1" originates from a ≤30 milliarcsecond diameter source whose position we determine to coincide within ± 0''15 with the apex of the cone structure seen in the optical narrow emission lines, as well as the location of the flat spectrum radio component SI and the 12 μm emission peak. We interpret the compact source as hot dust near the sublimation temperature within ∼ 1 pc of the true nucleus of the galaxy. The remaining 6% of the light in the central 1″ comes from a moderately extincted stellar core centered on the nuclear position and of intrinsic size ∼50 pc. We show that this nuclear stellar core is probably 5-16 × 108 yr in age and contributes at least 7% of the total nuclear luminosity of ~1 × 1011 L⊙. © 1997. The American Astronomical Society. All rights reserved.